PERTANGGUNGJAWABAN PIDANA DALAM TINDAK PIDANA SUAP (STUDI KASUS PUTUSAN NOMOR 13/PID.SUS-TPK/2022/PN.MTR) - Putri, Absonia Mebi Yunika (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The term "corruption" refers to ibias-based crime, and the impact that arises from the term "corruption" can have a significant impact on national immorality, democracy, economic and social welfare, as well as on justice and the prosperity of the people of Indonesia. In addition to that, there are a number of other criminal justice officials in Indonesia who are concerned about the Attorney General's Office or the Police, the role of the Indonesian Court of Mataram in law enforcement, especially in handling cases of serious criminal offenses against corruption , this can be seen from the cases of criminal acts of corruption that have been successfully uncovered by the iState Court of Mataram and the perpetrators of these acts of corruption have been prosecuted at the Corruption Court in Mataram, including those who have been detained